Morphosyntactic peculiarities of ditransitive constructions with the verb 'DAR' in Portuguese Sign Language - Choupina, Celda (2016)
In this study we analyze some morphosyntactic aspects of the verb DAR (to give) in LGP (Portuguese Sign Language) in simple declarative sentences, in particular, two properties: (i) the position of the arguments regarding the verb and (ii) the agreement of the verb with the internal arguments. We defend that the basic word order in ditransitive constructions is S V DO IO, although other syntactic processes, such as simple and double topicalization may, apparently, call into question the existence of that basic pattern.